2016
DOI: 10.3329/bsmmuj.v9i3.29459
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinically diagnosed lumbar intervertebral disc prolapse and magnetic resonance image findings

Abstract: <p>There are contradictory reports on the findings of magnetic resonance image (MRI) in lumbar intervertebral disc prolapse. A study was conducted on 54 patients using 3 of 4 clinical criteria (low back pain with radiation down to the lower limbs, radicular pain along specific dermatomes, positive straight leg raising test, presence of neurological symptoms and signs e.g. motor or sensory deficit and MRI of lumbosacral spine of the respondent). Evaluation of MRI of lumbosacral spine was done based on ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In the present study there is significant correlation between occupation of patient and development of lumbar disc prolapse with maximum patients were manual labourers which was also according to a study conducted by sharma et al [17] . In this study on total 60 patients 57% of patients were male population that means of male preponderance because of more outdoor activities by males also in relation to study by rahman MH in which there were 74.1% patients were male and 25.9% patients were female [18] .In this study conducted on 60 patients routine activity was hampered only in 30% patients which was according to the study did by Rainvillie et al [19] . In the present study this was found that the with increase in disc herniation level there is increase in neural canal compromise but this is against study conducted by rai et which found that there is no significant correlation between these two terms [20] .…”
Section: Discussionsupporting
confidence: 62%
“…In the present study there is significant correlation between occupation of patient and development of lumbar disc prolapse with maximum patients were manual labourers which was also according to a study conducted by sharma et al [17] . In this study on total 60 patients 57% of patients were male population that means of male preponderance because of more outdoor activities by males also in relation to study by rahman MH in which there were 74.1% patients were male and 25.9% patients were female [18] .In this study conducted on 60 patients routine activity was hampered only in 30% patients which was according to the study did by Rainvillie et al [19] . In the present study this was found that the with increase in disc herniation level there is increase in neural canal compromise but this is against study conducted by rai et which found that there is no significant correlation between these two terms [20] .…”
Section: Discussionsupporting
confidence: 62%
“…Several studies found the relationship between clinical features and MRI findings. These studies also gave contrasting reports and were inconclusive 26,28,29 .…”
Section: Fig 1: Prevalence Of Status Of Herniationmentioning
confidence: 99%